Biogenesis and Function of Multivesicular Bodies in Plant Immunity - Li, Xifeng; Bao, Hexigeduleng; Wang, Zhe; Wang, Mengxue; Fan, Baofang; Zhu, Cheng; Chen, Zhixiang (Frontiers in Plant Science, 2018)
Multivesicular bodies (MVBs) are specialized endosomes that contain intraluminal vesicles generated from invagination and budding of the limiting membrane. In the endocytic pathway, MVBs are late endosomes whose content can be degraded through fusion with lysosomes/vacuoles or released into the extracellular space after fusion with the plasma membrane. The proteins retained on the limiting membrane of MVBs can be delivered to the membrane of lysosomes/vacuoles or sorted back to the plasma membrane. It has been long suspected that MVBs might fuse with the plasma membrane to form paramural bodies in plant cells, possibly leading to release of building blocks for deposition of papillae and antimicrobial molecules against invading pathogens. Over the past decade or so, major progresses have been made in establishing the critical roles of MVBs and associated membrane trafficking in pathogen recognition, defense signaling and deployment of defense-related molecules during plant immune responses. Regulatory proteins and signaling pathways associated with induced biogenesis and trafficking of MVBs during plant immune responses have also been identified and characterized. Recent successful isolation of plant extracellular vesicles and proteomic profiling of their content have provided additional support for the roles of MVBs in plant-pathogen interactions. In this review, we summarize these important progresses and discuss how MVBs, particularly through routing of cellular components to different destinations, contribute to the complex network of plant immune system.